Creating and Managing Green Residential Interior Design in Baotou Inner Mongolia, China - Yongxia, Cao; Nasi, Nadia Binti Mohd (South Asian Journal of Social Sciences and Humanities, 2024)
Purpose/Background: As sustainability garners global attention, exploring green design in residential interiors is significant. This study examined the creation and management of green residential design in Baotou, China. Environmentally conscious interior design can improve residential satisfaction, health, and conservation. Methods: A qualitative approach involved semi-structured interviews with Baotou residents to gain insights into experiences with and perceptions of green residential design. Detailed interviews explored specific sustainable features residents valued along with challenges faced. Interview transcripts were systematically coded and subjected to rigorous thematic analysis. Findings: Analysis highlighted the rationale for implementing green elements in Baotou and their impacts on residential communities, individual wellbeing, and the environment. Findings offer concrete implications for stakeholders including architects, designers, and property managers seeking to create eco-conscious interiors. Conclusions: Dynamic policies on green design pose constraints to consistent implementation, impacting the feasibility of proposed decorative solutions. Still, findings demonstrate clear connections between sustainable features and increased residential quality, which can inform environmentally friendly urban development. Ongoing legal analysis and community consultation is critically needed to adapt strategies while meeting residents’ needs.